2009
DOI: 10.1017/s0016672309000214
|View full text |Cite
|
Sign up to set email alerts
|

Increased litter size and super-ovulation rate in congenic C57BL mice carrying a polymorphic fragment of NFR/N origin at theFecq4locus of chromosome 9

Abstract: By analysing N2 mice from a cross between the inbred C57BL strain B10.Q and the NMRI-related NFR/N strain, we recently identified a quantitative trait locus (QTL) influencing litter size. This locus is now denoted Fecq4, and it is present on the murine chromosome 9. In the present paper, we describe how the Fecq4 fragment originating form the NFR/N mouse strain will affect B10.Q mice by means of breeding capacity, super-ovulation rate and embryonic development in vitro. Our results show that both the breeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
2
3
1
Order By: Relevance
“…Therefore, ovulation and litter size are quantitative processes controlled by a complex interaction among multiple genes. The Bmp6 locus was not identified by the previous QTL linkage analyses as a candidate locus that determines ovulation rate or litter size [69][70][71][72][73]; however, the present study has clearly shown that a deletion in the Bmp6 gene does affect ovulation rate and litter size in mice. Therefore, Bmp6 is probably part of the complex genetic network that determines female fertility.…”
contrasting
confidence: 77%
See 1 more Smart Citation
“…Therefore, ovulation and litter size are quantitative processes controlled by a complex interaction among multiple genes. The Bmp6 locus was not identified by the previous QTL linkage analyses as a candidate locus that determines ovulation rate or litter size [69][70][71][72][73]; however, the present study has clearly shown that a deletion in the Bmp6 gene does affect ovulation rate and litter size in mice. Therefore, Bmp6 is probably part of the complex genetic network that determines female fertility.…”
contrasting
confidence: 77%
“…Each process is affected by multiple factors, including genetic variability as well as environmental influences. For example, previous studies have identified several quantitative trait loci (QTL) that determine hormone-induced ovulation rate or litter size in mice [69][70][71][72][73]. Therefore, ovulation and litter size are quantitative processes controlled by a complex interaction among multiple genes.…”
mentioning
confidence: 99%
“…Our results show high newly born number of treatment groups (T1,T2,T3,T4&T5) when compare them with C group, these results are accompanied with (29) who notice that superovulation by hormones treatment lead to increase of newly born number.…”
Section: Effect Of Hormonal Program On Number Of Newbornssupporting
confidence: 58%
“…6 Moreover, evidence for genes that also influence normal variation in fertility is provided by quantitative-trait loci (QTL) mapping studies in mice, flies, pigs, and cattle; these studies have identified genetic loci that affect reproductive characteristics in those species. [7][8][9][10][11][12][13][14][15] However, in most QTL mapping studies, the associated regions were too broad to allow for the discovery of specific genes that affect reproductive traits.…”
Section: Introductionmentioning
confidence: 99%